Arjen murtumia : nykytaide ottaa kantaa Kiasman kokoelmissa - Aarnio, Eija; Sakari, Marja; KIASMA (Museum of Contemporary Art), Helsinki (Helsinki : KIASMA (Museum of Contemporary Art) Helsinki, 2005)
Ahtila, Eija-Liisa ; Aiha, Martti ; Arminen, Tuija ; Duncker, Henrik ; Duncker, Maria ; Eva & Adele ; Friberg, Maria ; Gaál, Miklos ; Hákon, Hulda ; Halso, Ilkka ; Hamari, Mia ; Hausswolff, Annika von ; Heikkilä, Jussi ; Hiltunen, Heli ; Holmström, Gun ; Hölttä, Heini ; Huhta, Jari ; Hulkko, Irmeli ; Hytönen, Petri ; Hyttinen, Niilo ; Inkinen, Juha-Pekka ; Jämsä, Aarne ; Jämsä, Martti ; Jermolaewa, Anna ; Jokisalo, Ulla ; Kaila, Jan ; Kanervo, Marja ; Kentridge, William ; Korkeila, Jukka ; Kumpulainen, Hannele ; Larjosto, Harri ; Lehtinen, Jukka ; Lehtonen, Henrietta ; Niemelä, Jaakko ; Niemi-Junkola, Fanni ; Niskanen, Pekka ; Räbinä, Paavo ; Reinhard, Aurora ; Renqvist, Torsten ; Rheinsberg, Raffael ; Rist, Pipilotti ; Roos, Nina ; Ryöppy, Catarina ; Saarto, Ari ; Sarva, Sanna ; Savchenko, Igor ; Sierra, Santiago ; Silomäki, Jari ; Slaattelid, Mari ; Soinio, Kari ; Tammi, Pasi ; Tiisala, Eeva ; Toomik, Jaan ; Trimakas, Gintautas ; Tuominen, Anu ; Tuunanen, Yrjö ; Valiukaite-Mikolaitiene, Elena ; Whitehead, Oliver ; Ziura, Darius
Bibliog. p. 127-130
Publication on the occasion of the exhibition 'Arjen murtumia = Fractures of life' at the KIASMA (Museum of Contemporary Art) in Helsinki, 02.04.2005-27.11.2005
boek